Influences of zonation on water fertility and structure communities of phytoplankton and benthos in Batukaras Mangrove Forest, Pangandaran District, Indonesia (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Pratiwi D, Oktavia D, Sumiarsa D, Sunardi S. 2023. Influences of zonation on water fertility and structure communities of phytoplankton and benthos in Batukaras Mangrove Forest, Pangandaran District, Indonesia. Biodiversitas 24: 4978-4988. Mangrove forests are coastal areas with several advantages, including access to natural resources that other regions do not provide. Pangandaran has mangrove forest areas, namely Batukaras mangroves, located in Batukaras Village, Pangandaran, West Java, Indonesia. This study aims to identify the primary productivity and community structure of phytoplankton and benthos as one of the natural resources in the Batukaras mangrove with different zone patterns of mangrove (seaward and landward). The purposive sampling method determined the observation stations based on the vegetation density. The obtained data of Net Primary Productivity (NPP) was analyzed with the light and dark bottle (Winkler method). In addition, the data community structure of phytoplankton and benthos was analyzed using the Shannon Wienner diversity index (H'), equitability index (E), and Simpson dominance index (D). The results show that the NPP in seaward and landward are mesotrophic with values of 105.833 mgC/m3/h and 36.463 mgC/m3/h. The abundance of phytoplankton and benthos in seaward is 560 ind/m3 and 387 ind, while landward ranges from 1140 ind/m3 and 135 ind. Planktoniella sp. and Faunus ater dominated the community structure of phytoplankton and benthos seaward, while the landward location consisted of Oscillatoria sp. and Terebralia sulcata. The community structure of phytoplankton and benthos in seaward and landward has significant differences (
Keywords: Diversity, landward zone, seaward zone, tropic status, vegetation